Challenges Facing Heads of Schools in Performing Procurement Activities: A Case of Public Secondary Schools in Monduli District Arusha, Tanzania - Muhoja, Nestory Thomas; Mkulu, Demetria Gerold (International Journal of Humanities and Education Development (IJHED), 2020)
The purpose of this paper was to examine the challenges facing heads of schools in performing procurement activities in public secondary schools. The current study employed mixed research approach and convergent parallel design. A sample size of 198 respondents comprising of 152 teachers, 36 procurement committee members, 4 heads of school, 4 school bursars, 1 District education officer and 1 head of procurement management unit. Both probability and none probability sampling techniques were used to gather the participants. This study adopted cost-benefit analysis theory. Data were collected using questionnaires and in-depth interviews. Qualitative data were analyzed thematically and presented in themes and summarization while quantitative data were analyzed descriptively with the help of Statistical Package for Social Sciences version 20 and presented by charts, tables, percentages and frequencies. Quantitative instruments were validated using split half and a coefficient of 0.79 was obtained whereas content and face validity used to validate the quantitative instrument. Credibility was used to validate the qualitative tools while, reliability of qualitative instrument was ensured through the use of dependability. The findings revealed that challenges facing heads of schools included lack of procurement personnel, inadequate knowledge, skills and experience on procurement, insufficient funds, political interference, and favouritism and nepotism. The study recommended that there should be efforts to overcome the challenges facing heads of schools so as to improve the procurement practices in secondary schools